2006
DOI: 10.1021/cg0506424
|View full text |Cite
|
Sign up to set email alerts
|

Crystals from Light:  Photochemically Induced Nucleation of Hen Egg-White Lysozyme

Abstract: In this paper, we demonstrate that the irradiation of a metastable supersaturated lysozyme solution by a light produced by a continuous 150 W Xe lamp induces nucleation and that the mechanism is photochemically induced by a one-photon process. The irradiation of lysozyme molecules produces residual tryptophan radicals, which enhance the attractive interactions between molecules in solution, as shown by dynamic light scattering measurements, and increase the nucleation rate of lysozyme. When the intermediate is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 30 publications
0
41
0
Order By: Relevance
“…The photochemical covalent-bonded dimer of HEWL is considered to enhance the nucleation because dimer formation by weak physical interactions (van der Waals force or hydrogen bond) is energetically unfavorable [13][14][15]. In our system, however, contribution of the dimers on nucleation is rather small, because the enhancement of nucleation by the laser irradiation of k = 260 nm was same as that of k = 780 nm (Figure 3c,f and Figure 4).…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…The photochemical covalent-bonded dimer of HEWL is considered to enhance the nucleation because dimer formation by weak physical interactions (van der Waals force or hydrogen bond) is energetically unfavorable [13][14][15]. In our system, however, contribution of the dimers on nucleation is rather small, because the enhancement of nucleation by the laser irradiation of k = 260 nm was same as that of k = 780 nm (Figure 3c,f and Figure 4).…”
Section: Discussionmentioning
confidence: 77%
“…However, the intensities of HEWL dimer band at 28 kDa increased. Okutsu et al reported that UV light irradiation produces the photochemical covalent-bonded protein dimers, which enhance nucleation [13][14][15]. Figure 5b shows the closeup of the bands at 28 kDa and band intensity.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations